Comparing numerical methods for the solutions of systems of ordinary differential equations - Shawagfeh, N; Kaya, D (Pergamon-Elsevier Science Ltd, 2004)
In this article, we implement a relatively new numerical technique, the Adomian decomposition method, for solving linear and nonlinear systems of ordinary differential equations. The method in applied mathematics can be an effective procedure to obtain analytic and approximate solutions for different types of operator equations. In this scheme, the solution takes the form of a convergent power series with easily computable components. This paper will present a numerical comparison between the Adomian decomposition and a conventional method such as the fourth-order Runge-Kutta method for solving systems of ordinary differential equations. The numerical results demonstrate that the new method is quite accurate and readily implemented. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Adomian decomposition method; fourth-order Runge-Kutta method; system of ordinary differential equations